Assessment of the mutagenic potential of Cr(VI) in the oral mucosa of Big Blue® transgenic F344 rats. (22nd May 2015) - Thompson, Chad M.; Young, Robert R.; Suh, Mina; Dinesdurage, Harshini R.; Elbekai, Reem H.; Harris, Mark A.; Rohr, Annette C.; Proctor, Deborah M.
<x xml:space="preserve">Abstract</x> Exposure to high concentrations of hexavalent chromium [Cr(VI)] in drinking water was associated with an increased incidence of oral tumors in F344 rats in a 2‐year cancer bioassay conducted by the National Toxicology Program. These tumors primarily occurred at 180 ppm Cr(VI) and appeared to originate from the gingival mucosa surrounding the upper molar teeth. To investigate whether these tumors could have resulted from a mutagenic mode of action (MOA), a transgenic mutation assay based on OECD Test Guideline 488 was conducted in Big Blue® TgF344 rats. The mutagenic oral carcinogen 4‐nitroquinoline‐1‐oxide (4‐NQO) served as a positive control. Mutant frequency was measured in the inner gingiva with adjacent palate, and outer gingiva with adjacent buccal tissue. Exposure to 10 ppm 4‐NQO in drinking water for 28 days increased mutant frequency in the cII transgene significantly, from 39.1 ± 7.5 × 10−6 to 688 ± 250 × 10−6 in the gingival/buccal region, and from 49.8 ± 17.8 × 10−6 to 1818 ± 362 × 10−6 in the gingival/palate region. Exposure to 180 ppm Cr(VI) in drinking water for 28 days did not significantly increase the mutant frequency in the gingival/buccal (44.4 ± 25.4 × 10−6) or the gingival/palate (57.8 ± 9.1 × 10−6) regions relative to controls. These data indicate that high (∼180, 000 times expected human exposure), tumorigenic concentrations of Cr(VI) did not significantly increase mutations in the gingival epithelium, and suggest that Cr(VI) does not act by a mutagenic MOA in the rat oral cavity. Environ. Mol. Mutagen. 56:621–628, 2015. © 2015 Wiley Periodicals, Inc.